Teaching English by Using YouTube in SMP IT Al-Afkari Deliserdang - Pasaribu, Gumarpi Rahis; Salmiah, Maryati; Sulistyaningrum, Siti Drivoka; Napitupulu, Fenty Debora (Regalia Institute, 2023)
This study aimed to explore the use of YouTube videos in learning English, students' conclusions about improving their English skills after using YouTube videos, problems faced by teachers and students, and student acceptance of the use of YouTube videos. Bottom. While studying English. The respondents were 7 English teachers from the eighth exam and 40 second-year students from the 8th. This study used a mixed graft method as the study design. Information was collected through the dissemination of surveys. Our investigation revealed the following: a) The trainer was able to implement this process because he used a YouTube video technique to train some skills in English. Students had positive opinions about changes in English learning. Students also said that following this procedure could reduce boring classes and increase their motivation to learn English. There were issues in designing the evaluation process when implementing the YouTube video strategy, such as internet connectivity and student readiness. Teachers had to create procedures to help students better understand the topic. As a result of these reflections, her use of YouTube recordings in teaching and learning English positively impacted students' English proficiency and assisted teachers in communicating topics to students. The results were consistent with past reflection results. Was consistent. Aside from that, this program made some discoveries, such as teachers' practice methods, students' opinions on improving their English skills, and students' evaluations of the introduction of YouTube videos.